MEDICAL SNORKEL-MASK: A REUSABLE PERSONAL PROTECTIVE EQUIPMENT FOR HEALTH WORKERS - Manaf, Hafizh Al-Ghifari; Suyudi, Muhammad Arsy Reza; Razaan, Muhammad Farraas; Praba, Venansya Maulina; Al Mufid, Shofiuddin; Adhima, Fauziah; Nugroho, Puguh Setyo (Journal of Community Medicine and Public Health Research, 2022)
Covid-19 is a new disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The increasing number of cases of Covid-19 has made it difficult for hospitals to handle it, and health workers are at a higher risk of infection by SARS-CoV-2 and urgently need Personal Protective Equipment (PPE) to protect themselves and minimize the spread of the virus. However, the usage of PPE especially face-masks often causes discomfort. Therefore, a new type of face mask has emerged, namely the medical snorkel mask. This mask is designed to cover the entire face and is made by modifying the air circulation section by adding an air filter. The filter used is PALL Ultipor 25 with a HEPA filter capable of filtering up to 0.3 microns in size and has an efficiency of 99.99%. Medical snorkel mask that is used properly are quite efficient in preventing the transmission of Covid-19, with a fitting factor of 142 from pass level 100. This mask also has passed the CO2 toxicity test. The advantages of a medical snorkel mask include protecting the entire face from infectious droplets, preventing direct hand contact with the face, being reusable, and being equipped with an effective air filter by minimizing the potential for filtrate malfunction. Some of the disadvantages of this mask include interfering with the communication process, cannot being used in conjunction with glasses, a buildup of CO2, increasing the work of breathing, and limiting vision. However, some of these weaknesses can be minimized by modifying the mask and maintaining an optimal barrier system. Given the high level of effectiveness and efficiency, medical snorkel masks can be a novel solution to overcome the discomfort of using PPE for health workers in Indonesia. Hopefully, it can reduce the morbidity and mortality of health workers due to exposure to Covid-19.